Comparison of Maternal, Perinatal, and Neonatal Outcomes of Asymptomatic and Symptomatic Pregnant Women with Coronavirus Disease-2019 - Tayfun VURAL; Burak BAYRAKTAR; Suna YILDIRIM KARACA; Ozan ODABAS; Nisel YILMAZ; Pınar SAMLIOGLU; Mehmet OZEREN (Medeniyet Medical Journal)
Objective: This study aimed to compare the postpartum outcomes of asymptomatic and symptomatic patients with coronavirus disease-2019 (COVID-19). Methods: This retrospective cohort study included pregnant women with COVID-19. Pregnant women were categorized into two sets as asymptomatic and symptomatic according to their clinics at the time of application. COVID-19 was diagnosed using the real-time reverse transcriptase-polymerase chain reaction on the oropharyngeal and nasopharyngeal swabs. Asymptomatic and symptomatic patients were compared in terms of maternal and perinatal outcomes. Results: Our study population consisted of 20 asymptomatic and 41 symptomatic patients with laboratory-confirmed COVID-19. The rate of primary cesarean section was more than twice in the symptomatic group (51.2%) than that of the asymptomatic group (20%) (p=0.019). Both groups are quite similar in terms of maternal [respiratory support, COVID-19-related treatment, and intensive care unit (ICU) admission], perinatal (preterm delivery, preterm premature rupture of membrane, preeclampsia, and mode of delivery), and neonatal outcomes [birth weight, Apgar scores, neonatal ICU (NICU) admission]. The rate of total cesarean section in the asymptomatic group (75%) was statistically similar to the symptomatic group (83%) (p=0.464). The NICU admission rate was found to be similar in the asymptomatic (54.2%) and symptomatic groups (50%) (p=0.858). However, NICU admissions were more frequent in the symptomatic group due to respiratory distress (p=0.032). The breastfeeding rate is higher in the asymptomatic pregnant group as expected (p=0.015). Additionally, the ferritin level was significantly lower in the asymptomatic group (p=0.006). Conclusions: The rate of primary cesarean section is quite high in symptomatic patients with COVID-19. Additionally, the total cesarean section rate was extremely high in both groups. We expected more adverse outcomes in symptomatic patients; however, we found similar maternal, perinatal, and neonatal outcomes between both groups.